STUDI KASUS KONSELING PASTORAL TERHADAP SEORANG IBU YANG MENGALAMI LUKA BATIN. - Deni Waljufri (PT. Giat Konseling Nusantara, 2026)
The aim of this research is to observe and describe the condition of a mother who experiences emotional pain. The emotional pain she experienced resulted in physical suffering. The research method used in this research is the Pastoral Case Study Method. The theories used in this research are pastoral counseling, emotional wounds, the mother's personality and theology of forgiveness. The research results obtained from this research are that the emotional wounds experienced by a mother have a negative impact on her life. The pastoral action taken is to reveal and acknowledge the emotional wounds that the woman has experienced and be willing to forgive the past that has hurt her. This case actually happens a lot in congregational life, and the church must pay attention to it and provide assistance to it.